Examining Role Conflict as a Mediator in the Effect of Workload on Burnout among Part-Time Working Students in Padang (Universitas Pendidikan Indonesia (UPI), 2025)
Recent socioeconomic developments in Indonesia have transformed students’ lifestyles, including how they meet their financial needs. Rising education costs have strained students’ financial resources, prompting some of them to seek additional income through part-time work. However, these part-time jobs present challenges such as the need to manage workloads alongside academic responsibilities. If left unaddressed without adequate recovery, this situation can lead to chronic stress, a condition known as burnout. Therefore, this study examines the influence of workload on burnout, mediated by role conflict. This study utilized 91 respondents who were part-time working students in the city of Padang, and the data was analyzed using the SmartPLS software. The findings indicate that: 1) workload has a positive and significant effect on burnout, 2) workload has a positive and significant effect on role conflict, 3) role conflict has a positive and significant effect on burnout, 4) and role conflict positively and significantly mediates the effect of workload on burnout.